Openness, Pedagogy, and Parenthood in Gaston Bachelard - Vydra, Anton (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2022)
There is a link between Gaston Bachelard’s parental and pedagogical experiences, as well as between his writings on these themes and his epistemological ideas on new approaches in the sciences. Bachelard made an appeal to educational institutions and teachers to change their strictly, authoritative attitude towards students and substitute it by a new, still exacting yet also stimulating one. To be an inspiring pedagogue does not mean abandoning rigor and discipline. We could find three interesting issues in Bachelard’s thinking about the pedagogical mind and its psychoanalysis. First is the need for teacher “openness”. Assuming to be guardians of a treasury of knowledge, or omniscient epistemological “gods”, is not an appropriate pedagogical disposition for teachers vis-à-vis students. Secondly, if teachers change their attitudes toward scientific errors throughout history, they will be better prepared to work with students’ errors as well as their own. Errors are not a calamity, according to Bachelard; the real calamity would be inhibition from fear of error, and giving up the work. The third great theme of Bachelard’s idea of pedagogy is the “dialogical” approach – namely, discursivity. For the French philosopher, no rationalist is a loner but rather a participant in the scientific community. The “school” concept includes such a principle. Schools are not primarily buildings for Bachelard; they are “sites” where people work tirelessly together to attain knowledge. The rationalistic background of his thinking led him to understand the meaning of the school as a life-long practice. This does not mean that every pupil must become a teacher, but rather that a teacher must choose to become a permanent pupil. This rejuvenation is a key feature of Bachelard’s approach to pedagogy, and it also teaches him how to become a better parent. Finally, it opens up a philosophical question about freedom and respect. To allow students greater freedom in their paths toward knowledge, teachers must above all develop greater control over themselves and be able to judge their own pedagogical super-egos. That is the way toward becoming the exemplary beings or “super-persons” who, in Bachelard’s view, would serve as inspiring and stimulating voices for their pupils.